(untitled) (World Bulletin of Public Health, 2022)
High prevalence of hearing impairment (HI) in recent decades among diabetes has aroused the concern of researchers. Diabetes Mellitus (DM) is a serious chronic disease that has a large impact on the lives around the world. People with diabetes have twice the rate of hearing loss compared to people without diabetes.